Influence of Striatal Dopamine, Cerebral Small Vessel Disease, and Other Risk Factors on Age-Related Parkinsonian Motor Signs - Rosano, Caterina (J Gerontol A Biol Sci Med Sci, 2020)
OBJECTIVE: Parkinsonian motor signs are common and disabling in older adults without Parkinson’s disease (PD), but its risk factors are not completely understood. We assessed the influence of striatal dopamine levels, cerebral small vessel disease, and other factors on age-related parkinsonian motor signs in non-PD adults. METHODS: Striatal dopamine transporter (DAT) binding was quantified via [(11)C]-CFT positron emission tomography in 87 neurologically intact adults (20–85 years, 57.47% female) with concurrent data on: Unified Parkinson’s Disease Rating Scale motor (UPDRSm), white matter hyperintensities (WMH), and other risk factors (grip strength, vibratory sensitivity, cardio- and cerebro-vascular comorbidities). Sex-adjusted nonparametric models first estimated the associations of age, DAT, WMH, and other factors with UPDRSm; next, interactions of age by DAT, WMH, or other factors were tested. To quantify the influence of DAT, WMH, and other risk factors on the main association of age with UPDRSm, multivariable mediation models with bootstrapped confidence intervals (CI) were used. RESULTS: Older age, lower DAT, higher WMH, and worse risk factors significantly predicted worse UPDRSm (sex-adjusted p < .04 for all). DAT, but not WMH or other factors, positively and significantly interacted with age (p = .02). DAT significantly reduced the age-UPDRSm association by 30% (results of fully adjusted mediation model: indirect effect: 0.027; bootstrapped 95% CI: 0.0007, 0.074). CONCLUSIONS: Striatal dopamine appears to influence to some extent the relationship between age and parkinsonian signs. However, much of the variance of parkinsonian signs appears unexplained. Longitudinal studies to elucidate the multifactorial causes of this common condition of older age are warranted.